The Blackwoods Farm enquiry - Purser, Ann (Purser, Ann. Ivy Beasley mystery., 2014)
Interested in penning her memoirs, Ivy Beasley decides to take a creative writing course. But it's hard to find time to put pen to paper when this current chapter is so full of lies, jealousy and murder... Rumors are flying around the village of Barrington about Mrs. Winchen Blatch, a reclusive widow living alone in her old farmhouse. In the past few weeks, the widow claims she has been tormented by ghostly visitations, so she hires Ivy and her fellow investigators at Enquire Within to get to the bottom of the mystery. Ivy's new classes are very close to the widow's farmhouse, perfect for combining studying and snooping.